Student Perceptions Towards the use of YouTube as An Educational Tool for Learning and Tutorials - Maziriri, Eugine Tafadzwa; Gapa, Parson; Chuchu, Tinashe (International Journal of Instruction, 2020)
YouTube as an educational tool has been recently receiving a great deal of attention from researchers and teachers. The study in question therefore investigates this phenomenon. To this end, a modified conceptual model based on the technology acceptance model (TAM) was proposed to test student perceptions, attitudes and intentions to adopt YouTube as an educational tool. The study was quantitative in nature where 377 registered students from a selected university were chosen through non-probability sampling. In order to analyse the data SPSS 25 and AMOS 25 were utilised for descriptive statistics and structural equation modeling respectively. Perceived usefulness of YouTube and perceived ease of use where proposed as antecedents of attitudes and intentions while adoption of YouTube as an educational tool was anticipated to be the outcome. The main findings suggested that perceived usefulness was observed to have a more significant impact on student perceptions toward learning through YouTube in comparison to the perceived ease of use. In addition, it was also discovered that intention to use YouTube and adoption of YouTube as an educational tool had the strongest relationship of all tested hypotheses. Implications for educators and researchers were established from the findings. Thereafter, suggestions for further research were proposed.